Characterization of the Epileptogenic Phenotype and Response to Antiseizure Medications in Lissencephaly Patients - Proepper, Christiane R.; Schuetz, Sofia M.; Schwarz, Lisa-Maria; Au, Katja von; Bast, Thomas; Beaud, Nathalie; Borggraefe, Ingo; Bosch, Friedrich; Budde, Joerg; Busse, Melanie; Chung, Jena; Debus, Otfried; Diepold, Katharina; Fries, Thomas; Gersdorff, Gero von; Haeussler, Martin; Hahn, Andreas; Hartlieb, Till; Heiming, Ralf; Herkenrath, Peter; Kluger, Gerhard; Kreth, Jonas H.; Kurlemann, Gerhard; Moeller, Peter; Morris-Rosendahl, Deborah J.; Panzer, Axel; Philippi, Heike; Ruegner, Sophia; Toepfer, Carolina; Vieker, Silvia; Wiemer-Kruel, Adelheid; Winter, Anika; Schuierer, Gerhard; Hehr, Ute; Geis, Tobias (Neuropediatrics, 2024)
Background Patients with lissencephaly typically present with severe psychomotor retardation and drug-resistant seizures. The aim of this study was to characterize the epileptic phenotype in a genotypically and radiologically well-defined patient cohort and to evaluate the response to antiseizure medication (ASM). Therefore, we retrospectively evaluated 47 patients of five genetic forms (LIS1/PAFAH1B1, DCX, DYNC1H1, TUBA1A, TUBG1) using family questionnaires, standardized neuropediatric assessments, and patients' medical reports.Results All but two patients were diagnosed with epilepsy. Median age at seizure onset was 6 months (range: 2.1–42.0), starting with epileptic spasms in 70%. Standard treatment protocols with hormonal therapy (ACTH or corticosteroids) and/or vigabatrin were the most effective approach for epileptic spasms, leading to seizure control in 47%. Seizures later in the disease course were most effectively treated with valproic acid and lamotrigine, followed by vigabatrin and phenobarbital, resulting in seizure freedom in 20%. Regarding psychomotor development, lissencephaly patients presenting without epileptic spasms were significantly more likely to reach various developmental milestones compared to patients with spasms.Conclusion Classic lissencephaly is highly associated with drug-resistant epilepsy starting with epileptic spasms in most patients. The standard treatment protocols for infantile epileptic spasms syndrome lead to freedom from seizures in around half of the patients. Due to the association of epileptic spasms with an unfavorable course of psychomotor development, early and reliable diagnosis and treatment of spasms should be pursued. For epilepsies occurring later in childhood, ASM with valproic acid and lamotrigine, followed by vigabatrin and phenobarbital, appears to be most effective.
Keywords: lissencephaly; neuronal migration; antiseizure medication; LIS1/PAFAH1B1; DCX; epileptic spasms